1977
DOI: 10.1128/iai.16.1.203-212.1977
|View full text |Cite
|
Sign up to set email alerts
|

Decreased oral colonization of Streptococcus mutans during aging of Sprague-Dawley rats

Abstract: with 10% H2, 10% C02, and 80% N2 at 37°C. Concentrated and diluted cell suspensions were made by using the same medium without added carbohydrate.Animal inoculation and determination of im-203 on July 31, 2020 by guest http://iai.asm.org/ Downloaded from 204 VAN HOUTE, UPESLACIS, AND EDELSTEIN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…7 of conventional animals. It has been shown that the age of the tooth is critically important for susceptibility to colonization by S. mutans and the resultant formation of caries (22,32). It has been shown that in humans, high counts of salivary lactobacilli can be correlated with prevalance of dental caries (2).…”
Section: Caries Induction In Various Animal Species With a Strain Of mentioning
confidence: 99%
“…7 of conventional animals. It has been shown that the age of the tooth is critically important for susceptibility to colonization by S. mutans and the resultant formation of caries (22,32). It has been shown that in humans, high counts of salivary lactobacilli can be correlated with prevalance of dental caries (2).…”
Section: Caries Induction In Various Animal Species With a Strain Of mentioning
confidence: 99%
“…Ninety days after inoculation, all rats were killed by carbon dioxide inhalation and decapitated, and the heads were skinned. Three maxillary and three mandibular molars from two quadrants of the mouth were extracted, ground in tissue grinders, and cultured for enumeration of the test organism on the teeth as described earlier (21).…”
mentioning
confidence: 99%
“…At the end of the experiments, 30 days after inoculation, rats were killed for enumeration of the test organisms on the molars of all four quadrants as outlined earlier (21).…”
mentioning
confidence: 99%
“…Streptomycin-resistant (SR) mutants of S. mutans have been used in many investigations because they can be easily and sensitively quantitated in samples of mixed bacterial populations by use of media containing streptomycin (10,11,19,30,33). Studies which have relied upon use of SR mutants of S. mutans include those investigating: (i) implantation of the organism in the mouths of humans, primates, and rodents (6,8,11,19,21,24,36); (ii) its transmission between individuals (17); (iii) its interdental transmission (7); (iv) its ability to attach to teeth and other oral surfaces (6,31,33,35); (v) its cariogenic potential in animal models (3,10,11,19,24,29); and (vi) the effects of antibodies on its colonization and virulence (8,22,24,25,29). During the course of studying the colonization of gnotobiotic rats by S. mutans strains isolated from humans and rodents, we observed that SR mutants colonized less effectively than wild-type strains; the present report describes these studies.…”
mentioning
confidence: 99%